2004
DOI: 10.1074/jbc.m406753200
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein K Enhances Insulin-induced Expression of Mitochondrial UCP2 Protein

Abstract: The uncoupling protein 2, UCP2, is a member of a family of inner mitochondrial membrane ion carriers involved in a host of metabolic processes. UCP2 protein is encoded by nuclear genome, but the protein is found exclusively in the mitochondria. The heterogeneous nuclear ribonucleoprotein K (hnRNPK) is an RNA-binding protein involved in many processes that compose gene expression, including mRNA processing and translation. The yeast three-hybrid screen revealed K protein bound to ucp2 mRNA through sites located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 70 publications
(113 reference statements)
2
34
0
3
Order By: Relevance
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 85%
“…As K protein is upregulated in tumour cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004) and modulates the expression of genes involved in mitogenic responses (Michelotti et al, 1995(Michelotti et al, , 1996Mandal et al, 2001;Ostrowski et al, 2004), altering its properties and introduction of a new phosphorylation site could make K protein either more or less conducive for the cellular processes that lead to tumorigenic state. If so, identification of this novel tumour-associated K protein isoform may prove to be a useful diagnostic, prognostic and/or therapeutic indicator.…”
Section: P<005mentioning
confidence: 99%
“…mitochondria It has been established that insulin increases levels of mitochondrial hnRNP K protein [9]. To obtain more information on the mitochondrial topology of hnRNP K protein and its potential import mechanisms, we investigated the mitochondrial transport of hnRNP K protein using an in vitro mitochondrial import system with the protein synthesized in vitro by coupled transcription-translation.…”
Section: Insulin Increases Import Of Hnrnp K Protein Intomentioning
confidence: 99%
“…Murine hnRNP K protein cDNA was inserted into pAdTrack vector, and HTC-IR cells were transfected as previously described [9].…”
Section: Adenovirus Construction and Infectionmentioning
confidence: 99%
See 1 more Smart Citation